2020
DOI: 10.1101/2020.04.22.056606
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

C. elegansepisodic swimming is driven by multifractal kinetics

Abstract: Fractal scaling is a common property of temporal change in various modes of animal behavior. The molecular mechanisms of fractal scaling in animal behaviors remain largely unexplored. The nematode C. elegans alternates between swimming and resting states in a liquid solution. Here, we report that C. elegans episodic swimming is characterized by scale-free kinetics with long-range temporal correlation and local temporal clusterization, which is characterized as multifractal kinetics. Residence times in actively… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…These emergent Markov dynamics offer a promising and powerful demonstration of quantitative connections across the hierarchy of movement behavior generally exhibited by all organisms [88,112]. Particularly interesting future directions include the analysis of even longer dynamics in C. elegans [113][114][115][116], for which no canonical behavioral states have been described.…”
Section: Discussionmentioning
confidence: 99%
“…These emergent Markov dynamics offer a promising and powerful demonstration of quantitative connections across the hierarchy of movement behavior generally exhibited by all organisms [88,112]. Particularly interesting future directions include the analysis of even longer dynamics in C. elegans [113][114][115][116], for which no canonical behavioral states have been described.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that episodic swimming of animals is responsible for this loss of sensitivity in snapshots. Worms are highly active in the first few minutes after transfer into liquid buffer 18 . Shortly thereafter, episodic swimming begins as worms enter intermittent inactive states for short periods of time 19 .…”
Section: Resultsmentioning
confidence: 99%
“…The user can distribute this total based on the number of conditions, replicates, and rounds in their experiments. Each round can last up to 15 min before animals start to enter an inactive state 18 and need to be re-stimulated on a thermoshaker. A total of 20 snapshots per well (three rounds of snapshots) was sufficient for each condition's curling analysis ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%